Integrasi Estetika dan Etika dalam Profesionalisme Guru Tata Kecantikan - Norma Yunita; Kokom Komariah (Garina, 2026)
This study analyzes the integration of aesthetics and ethics in cosmetology education and its implications for strengthening the professionalism of cosmetology teachers. Cosmetology is often viewed as an applied field that primarily produces visual beauty through make-up, skin care, hair care, and cosmetic services. However, professional cosmetology practice also involves moral responsibility because it deals directly with the human body, personal identity, safety, comfort, and client trust. This article uses a normative qualitative method with conceptual and philosophical approaches through library research. The analysis is organized through three dimensions of philosophy of science: ontology, epistemology, and axiology. The findings show that, ontologically, cosmetology studies beauty and the human body not merely as physical objects, but as subjects with value, dignity, and diverse meanings. Epistemologically, cosmetology knowledge is constructed through the integration of scientific theory, practical skills, professional experience, sanitation principles, occupational safety, and service standards. Axiologically, cosmetology contains ethical values that guide beauty practices so that they remain honest, safe, responsible, and respectful of human dignity. The integration of aesthetics and ethics strengthens the role of cosmetology teachers as educators, professional models, and character builders in vocational education. Therefore, cosmetology learning should not only emphasize technical competence and visual results, but also internalize ethical awareness, reflective judgment, and responsibility in every stage of professional practice.